Hydrated Nucleus Pulposus Extrusion in Dogs: Thoracolumbar Compared to Cervical Cases - Kristiansen, K. V.; Schmökel, H.; Vermeire, S. (Veterinary and Comparative Orthopaedics and Traumatology, 2022)
Objective The aim of this study was to review and describe cases of thoracolumbar (TL) hydrated nucleus pulposus extrusion (HNPE) diagnosed with magnetic resonance imaging and surgery, and compare them to cases of cervical (C) HNPE.Study Design Retrospective, single-center study.Results Thirty-six dogs met the inclusion criteria. Fifteen cases were C and 21 TL. Thirteen dogs were chondrodystrophic breeds, mean body weight was 13 kg, median age was 7.5 years, and 30/36 were male. Fewer dogs were chondrodystrophic in the C group compared with the TL group (p = 0.022). More than 90% had an acute onset, and strong activity was more often reported in the TL group. TL HNPE was more often painful, and extruded disc material more often lateralized (p = 0.017). Median Modified Frankel Score at presentation was 3 and 72.2% were non-ambulatory. More TL HNPE (11/21) were treated surgically compared with C HNPE (4/15). Treatment choice was correlated with spinal cord compression (p = 0.0075). Median Modified Frankel Score improved during hospitalization (p = 0.002) and there was no difference in outcome between C and TL HNPE or conservative and surgical treatment. Mean follow-up time was 33 days. All patients were ambulatory at follow-up.Conclusion This study suggests that the HNPE is not limited to the C vertebral column of dogs and can occur in the TL vertebral column as well. Dogs with TL HNPE show spinal hyperesthesia more often and extruded nucleus material is more often lateralized. Outcome is similar to what has previously been described for C HNPE.
Keywords: hydrated nucleus pulposus extrusion; intervertebral disc extrusion; paresis; paralysis; dog